2005
DOI: 10.1038/ja.2005.25
|View full text |Cite
|
Sign up to set email alerts
|

Prunustatin A, a Novel GRP78 Molecular Chaperone Down-regulator Isolated from Streptomyces violaceoniger

Abstract: In the course of our screening program for regulators of a molecular chaperone GRP78 expression, we isolated a novel inhibitor of GRP78 expression, designated as prunustatin A, from Streptomyces violaceoniger 4521-SVS3. The structure of prunustatin A was determined by a series of NMR analyses to be an oxidized type of the neoantimycin family. Prunustatin A inhibited the expression of GRP78 induced by 2-deoxyglucose in human fibrosarcoma HT1080 cells accompanied by global cell death without showing cytotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 8 publications
0
33
0
Order By: Relevance
“…Examples are arctigenin [167], deoxyverrucosidin [168], efrapeptin J [169], analogs of JBIR [170], piericidin A [171], prunustatin A [172], pyrvinium [173], rottlerin [174], valinomycin [175], and versipelostatin [176]. Collectively, these compounds are considered GRP78 downregulators, because they were shown to block the adaptive induction of GRP78 transcription in response to hypoglycemia.…”
Section: Er Stress In Cancermentioning
confidence: 99%
“…Examples are arctigenin [167], deoxyverrucosidin [168], efrapeptin J [169], analogs of JBIR [170], piericidin A [171], prunustatin A [172], pyrvinium [173], rottlerin [174], valinomycin [175], and versipelostatin [176]. Collectively, these compounds are considered GRP78 downregulators, because they were shown to block the adaptive induction of GRP78 transcription in response to hypoglycemia.…”
Section: Er Stress In Cancermentioning
confidence: 99%
“…Administration of EGCG has shown re-gain of sensitivity to the topoisomerase inhibitor etoposide in breast cancer cells (Ermakova et al, 2006). Moreover it has been shown that several cytotoxins inhibit GRP78 either by direct cleavage, like Subtilase AB5 derived from E. coli (Paton et al, 2006), or reducing its expression levels like Versipelostatin (derived from Streptomyces versipellis ; Matsuo et al, 2009) or Prunustatin A, a compound isolated from Streptomyces violaceusniger (Umeda et al, 2005). …”
Section: Targeting Grp78/bip In Refractory Cancersmentioning
confidence: 99%
“…Planar structures for SW-163A ( 9 ) and SW-163B ( 10 ) were reported in 2001 9 from a Japanese soil Streptomyces sp. (SNA15986), while the planar structures for prunustatin A ( 11 ), and JBIR-04 ( 12 ) and JBIR-05 ( 13 ), were reported in 2005 10 and 2007 11 respectively from the Okinawan soil Streptomyces violaceoniger (4521-SVS3), as down-regulators of the molecular chaperone GRP-78. The absolute configurations of 9 and 11 were subsequently determined in 2007 12 by chemical degradation and derivatization.…”
mentioning
confidence: 99%